Radiative cooling dynamics of anthracene cations stored in DESIREE studied via the time evolution of 2-photon-absorption induced dissociation rate. Issue 23 (January 2020) - Bernard, J; Ji, M C; Martin, S; Wenzel, G; Al-Mogeeth, A; Stockett, M H; Schmidt, H T; Zettergren, H; Joblin, C
Synopsis: Anthracene cations (C14 H10 + ) have been stored in the cryogenic (13 K) electrostatic storage ring DESIREE in Stockholm to study their radiative cooling dynamics on a long time scale up to 2 s. By monitoring the laser-induced delayed dissociation curves during the storage, the evolution of the dissociation rate was obtained. Its decrease as a function of time is closely related to the time evolution of the internal energy distribution of the stored anthracene cations and consequently to the energy loss due to radiative cooling, including both Poincaré and infrared fluorescences.